Pushing the Limits: Spinal Anesthesia in Children Undergoing Extended Urologic Surgeries - Evelyn Tenggara; Khildan Miftahul Firdaus (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Spinal Anesthesia (SA) is a promising alternative to General Anesthesia (GA) in pediatric surgery, offering advantages in respiratory safety, hemodynamic stability, and better perioperative pain control. However, it remains underused in routine practice, often due to concerns about its limited duration of block (<90 minutes). Objective: This case report aimed to explore the application of SA in pediatric patients of different ages and to highlight its potential role as an alternative to GA. Case Series: We reported 3 cases of SA used in pediatric patients of different ages who underwent urologic surgeries at Airlangga University Hospital. One child had intermittent asthma, while two were obese. All patients received SA with Bupivacaine, combined with different intravenous adjuvants. Intraoperative hypotension requiring sympathomimetic support occurred in the oldest child. The longest duration of spinal block was 240 minutes, and postoperative pain was mild in all three patients, without the need for rescue analgesia. No Perioperative Respiratory Adverse Events (PRAEs) occurred, and no conversion to GA was required. Discussion: SA in pediatric patients provided good perioperative pain control without the need for airway manipulation, thereby reducing the risk of airway related complications, which is particularly beneficial in patients with high-risk airway. Younger children tended to demonstrate more stable hemodynamic responses during SA due to their immature sympathetic nervous system. The use of intravenous adjuvants in SA prolonged the spinal block duration and improved block quality, while potentially reducing the toxicity of local anesthetic agent used. Conclusion: In these cases, SA was shown to be a safe and beneficial anesthetic technique for pediatric patients undergoing urologic surgery.